Hydrogen migration within a water molecule: formation of HD+ upon irradiation of HOD with intense, ultrashort laser pulses. (11th July 2017) - Mathur, Deepak; Dharmadhikari, Aditya K; Dharmadhikari, Jayashree A; Vasa, Parinda
Abstract: We have carried out velocity map imaging experiments on HOD molecules irradiated by 10 fs long pulses of intense (∼1 PW cm −2 ) laser light (800 nm). We have detected HD + ions as a signature of unimolecular hydrogen migration within the water molecule; ion momentum maps measured at different laser polarizations yield evidence that such hydrogen migration occurs on ultrafast timescales. We have been able to utilize the momentum maps to deduce that (i) the HD + ion that is formed is vibrationally excited, and (ii) that the electronic state of the precursor HOD 2+ dication has an essentially linear geometrical structure with elongated O–H and O–D bonds. Our results are in agreement with expectations from ab initio quantum chemical computations of potential energy surfaces of the lowest-energy states of HOD, HOD + and HOD 2+ .